The Private Law in the Legal System - Roppo, Vincenzo (2015)
In this article, the author introduces the main features and fundamentals of Private Law. Then, he makes a brief tour of the areas covered by private law within the system. Finally, through a comparison between the operation of private law and public law, the different logic to which each responds is emphasized.